General solution of second order fractional differential equations - Ilie, Mousa; Biazar, Jafar; Ayati, Zainab (International Journal of Applied Mathematical Research, 2018)
Fractional differential equations are often seeming perplexing to solve. Therefore, finding comprehensive methods for solving them sounds of high importance. In this paper, a general method for solving second order fractional differential equations has been presented based on conformable fractional derivative. This method realizes on determining a general solution of homogeneous and a particular solution of a second order linear fractional differential equations. Furthermore, a general solution has been developed for fractional Eulerâ€™s equation. For more explanation of each part, some examples have been solved.Â